The differential ability of two species of seagrass to use carbon dioxide and bicarbonate and their modelled response to rising concentrations of inorganic carbon - Maberly, Stephen Christopher; Stott, Andrew W.; Gontero, Brigitte (Frontiers in Plant Science, 2022)
Seagrass meadows are one of the most productive ecosystems on the planet, but their photosynthesis rate may be limited by carbon dioxide but mitigated by exploiting the high concentration of bicarbonate in the ocean using different active processes. Seagrasses are declining worldwide at an accelerating rate because of numerous anthropogenic pressures. However, rising ocean concentrations of dissolved inorganic carbon, caused by increases in atmospheric carbon dioxide, may benefit seagrass photosynthesis. Here we compare the ability of two seagrass from the Mediterranean Sea, Posidonia oceanica (L.) Delile and Zostera marina L., to use carbon dioxide and bicarbonate at light saturation, and model how increasing concentrations of inorganic carbon affect their photosynthesis rate. pH-drift measurements confirmed that both species were able to use bicarbonate in addition to carbon dioxide, but that Z. marina was more effective than P. oceanica. Kinetic experiments showed that, compared to Z. marina, P. oceanica had a seven-fold higher affinity for carbon dioxide and a 1.6-fold higher affinity for bicarbonate. However, the maximal rate of bicarbonate uptake in Z. marina was 2.1-fold higher than in P. oceanica. In equilibrium with 410 ppm carbon dioxide in the atmosphere, the modelled rates of photosynthesis by Z. marina were slightly higher than P. oceanica, less carbon limited and depended on bicarbonate to a greater extent. This greater reliance by Z. marina is consistent with its less depleted 13C content compared to P. oceanica. Modelled photosynthesis suggests that both species would depend on bicarbonate alone at an atmospheric carbon dioxide partial pressure of 280 ppm. P. oceanica was projected to benefit more than Z. marina with increasing atmospheric carbon dioxide partial pressures, and at the highest carbon dioxide scenario of 1135 ppm, would have higher rates of photosynthesis and be more saturated by inorganic carbon than Z. marina. In both species, the proportional reliance on bicarbonate declined markedly as carbon dioxide concentrations increased and in P. oceanica carbon dioxide would become the major source of inorganic carbon.